The Assessment of the Green Development of the Tobacco Industry Using a Multicriteria Method - Lapinskiene, Giedrė; Blazaitis, Martynas; Gedvilaite, Dainora; Slavinskaite, Neringa (Emerging Science Journal, 2025)
The tobacco industry is heavily regulated due to the significant health implications associated with tobacco use. The industry also involves numerous stakeholders, including farmers, manufacturers, distributors, retailers, regulators, and consumers. The aim of this research is to select the most relevant environmental criteria for the green development of the tobacco industry. This article uses Analytical Hierarchy Process (AHP) methods to create a hierarchical structure of the criteria and subcriteria necessary for green business development, establishing the relative weights of these subcriteria to find the areas in which attention and resources are most urgently required. The assessment of the concordance of expert opinions shows a satisfactory level of agreement. The article advances a more comprehensive view towards the evaluation of green criteria that are significant for the whole industry, seeking to highlight the need to think holistically. According to the views of experts, the most significant sub-criteria for the green development of the tobacco industry are increasing energy efficiency; safeguarding against hazardous wastewater in the environment; reducing the content of hazardous materials used in products; improving air, land, and water quality where economic activity takes place; sustainable forest management; eco-design, especially for efficient material use, biodegradability, and recyclability; and collaboration with suppliers. The entire industry should collaborate in seeking global green development by gradually investing in the improvement of green criteria. Doi: 10.28991/ESJ-2025-09-01-018 Full Text: PDF